Response to Comment by Zeebe and Tyrrell on "The Effects of Secular Calcium and Magnesium Concentration Changes on the Thermodynamics of Seawater Acid/Base Chemistry: Implications for the Eocene and Cretaceous Ocean Carbon Chemistry and Buffering". Issue 5 (16th May 2018) - Hain, Mathis P.; Sigman, Daniel M.; Higgins, John A.; Haug, Gerald H.
Key Points: Suspect parameters were changed to new reference The main results of original study hold true We demonstrate skill of MyAMI model, which is superior to existing correction factors